1970
DOI: 10.1115/1.3445300
|View full text |Cite
|
Sign up to set email alerts
|

Flow Through Cascades of Slotted Compressor Blades

Abstract: The performance of axial flow compressors can be improved when it becomes possible to achieve higher loading per stage than currently attainable. The major obstacles to attaining this objective are the limitations on loading in the end wall region and the limited range of operating incidence of compressor blades. A possible method of achieving a wide range of operating incidence is the use of slotted or multibody airfoils. An incompressible, two-dimensional, potential flow analysis for thick, highly cambered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The experimental results showed that the slot suppressed flow separation in the middle section of the blade but had no positive effect on corner flow control. 1 Mikolajczak et al 2 and Fottner 3 experimentally investigated flow fields in cascades with slotted blades, and the results showed that the flow loss control was not only unsatisfactory but also had a negative effect (the loss increased). Sturm et al 4 hypothesized that the low speed of the slot outlet caused these suboptimal results and proposed using an external air source to form jets to actively control the boundary layer on the blade suction surface, with the jet speed equivalent to the local mainstream speed and the jet direction as parallel to the mainstream direction as possible.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the slot suppressed flow separation in the middle section of the blade but had no positive effect on corner flow control. 1 Mikolajczak et al 2 and Fottner 3 experimentally investigated flow fields in cascades with slotted blades, and the results showed that the flow loss control was not only unsatisfactory but also had a negative effect (the loss increased). Sturm et al 4 hypothesized that the low speed of the slot outlet caused these suboptimal results and proposed using an external air source to form jets to actively control the boundary layer on the blade suction surface, with the jet speed equivalent to the local mainstream speed and the jet direction as parallel to the mainstream direction as possible.…”
Section: Introductionmentioning
confidence: 99%